Analisis Z-Score Untuk Memprediksi Tingkat Kebangkrutan Perusahaan (Studi Pada Industri Farmasi di Bursa Efek Indonesia Periode 2012-2014) - Himmiyatul Amanah Jiwa juwita (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
This study aims to determine the level of corporate bankruptcy using model analysis Altman Z-Score on pharmaceutical companies in Indonesia Stock Exchange (IDX) 2012-2014. The study population was all of the Pharmaceutical Industry with a sample of eight pharmaceuticalscompanies in the Indonesia Stock Exchange (IDX) in accordance with predetermined criteria. The results of this study indicate that the Altman Z-Score model can be implemented to detect the possibility of bankruptcy in the pharmaceutical company in Indonesia Stock Exchange (IDX). Altman Z-Score model and discriminant analysis do not have the same results in predicting bankruptcy in eight pharmaceutical companies because there is a miss classification in one company out of eight companies. The results of the Z-Score using discriminant analysis is able to classify a pharmaceutical company in two groups, that are healthy and gristle to bankruptcy.Keywords: pharmaceutical company, Bankruptcy Prediction, Altman Z-score model